2018
DOI: 10.1039/c7nj03736h
|View full text |Cite
|
Sign up to set email alerts
|

Activity coefficients in deep eutectic solvents: implications for the solvent extraction of metals

Abstract: On the difference in the activity coefficient between aqueous sodium chloride and a deep eutectic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…One example are deep eutectic solvents (DES), [43] which since the beginning of last decade generated great interest [44] and find a wide range of applications, such as metal extraction processes. [45] In this article, we apply the quantum cluster approach to binary mixtures of methanol with different alcohols. In particular, we investigate the effect of molecule size and branching on the deviation from ideal behavior for small size alcohols (one to four carbon atoms).…”
Section: Introductionmentioning
confidence: 99%
“…One example are deep eutectic solvents (DES), [43] which since the beginning of last decade generated great interest [44] and find a wide range of applications, such as metal extraction processes. [45] In this article, we apply the quantum cluster approach to binary mixtures of methanol with different alcohols. In particular, we investigate the effect of molecule size and branching on the deviation from ideal behavior for small size alcohols (one to four carbon atoms).…”
Section: Introductionmentioning
confidence: 99%
“…In a further study it was shown that identical behaviour was exhibited with a series of three ¶ very different solvent extraction systems. 38 At the start of our experimental work we attempted to measure data for a grid of four metals with three extraction reagents. We choose to use two ''solvating'' extraction agents which act as Lewis bases (cyanex 923 and the malonamides) and a dilute solution of an ionic liquid (aliquat 336) in an aromatic solvent.…”
Section: Resultsmentioning
confidence: 99%
“…We can make this equation slightly more simple by adsorbing the Debye-Hückel term into a constant C 0 0 0 together with C 00 if we maintain a constant ionic strength. This then allows us to write eqn (38) for this special case.…”
mentioning
confidence: 99%
“…The increased activity coefficient of chloride anions in DES phase with lower water content could result in the greater competition abilities of chloride anions against the anionic complexes from the organic phase to form the unextractable metal-chloride complexes, and remain in the DES phase. 172 More recently, Foreman and co-workers performed the solvent extraction of a selection of metals ( e.g. , Au, Pd, Tc, In and Re) in mixtures of a chloride rich DES ( i.e.…”
Section: Current Applications Of Des For Metal Recovery and Separatio...mentioning
confidence: 99%